2023
DOI: 10.1001/jama.2023.9350
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Whole-Genomic Sequencing and a Targeted Neonatal Gene Panel in Infants With a Suspected Genetic Disorder

Abstract: ImportanceGenomic testing in infancy guides medical decisions and can improve health outcomes. However, it is unclear whether genomic sequencing or a targeted neonatal gene-sequencing test provides comparable molecular diagnostic yields and times to return of results.ObjectiveTo compare outcomes of genomic sequencing with those of a targeted neonatal gene-sequencing test.Design, Setting, and ParticipantsThe Genomic Medicine for Ill Neonates and Infants (GEMINI) study was a prospective, comparative, multicenter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…We describe the first documented occurrence of an inherited CDK8 ‐associated disease variant in a child–parent pair (child: NM_001260.3; parent: NM_001260.2). All documented cases of CDK8 ‐related syndromes to date have arisen de novo (Table S1) (Aggarwal et al, 2020; Calpena et al, 2019; Halfmeyer et al, 2023; Maron et al, 2023; Miyamoto et al, 2021; Uehara et al, 2020); 13 different heterozygous variants have been identified in 18 unrelated patients. This case documents parental inheritance of a CDK8 pathogenic variant which can affect genetic counseling and recurrence risk in other family members.…”
Section: Discussionmentioning
confidence: 99%
“…We describe the first documented occurrence of an inherited CDK8 ‐associated disease variant in a child–parent pair (child: NM_001260.3; parent: NM_001260.2). All documented cases of CDK8 ‐related syndromes to date have arisen de novo (Table S1) (Aggarwal et al, 2020; Calpena et al, 2019; Halfmeyer et al, 2023; Maron et al, 2023; Miyamoto et al, 2021; Uehara et al, 2020); 13 different heterozygous variants have been identified in 18 unrelated patients. This case documents parental inheritance of a CDK8 pathogenic variant which can affect genetic counseling and recurrence risk in other family members.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, rapid genome sequencing in select cohorts of CHD patients identified clinically actionable results, in 27-46% of patients, and surpassed CMA in head-to-head comparisons [57][58][59]. However, other studies highlight limitations, including the burden of interpreting variants of uncertain significance, with differences in variant interpretation up to 43% [60]. Furthermore, while the coverage of genome sequencing is superior to exome sequencing, there are still gaps in genome sequencing coverage [55,61].…”
Section: Genomic Testing With Genome Sequencingmentioning
confidence: 99%
“…Whole genome sequencing and targeted neonatal gene panels can support rapid diagnosis, with turnaround times being as short as 4 days [95,96]. A point-of-care, swab-based genetic test device has recently been developed, which can detect the m.1555 A > G variant implicated in development of deafness in babies who are treated with gentamicin.…”
Section: Genetic Testingmentioning
confidence: 99%